A Conceptual Framework for Measuring Readiness for Change in Business: Theoretical Perspective and Practical Implications - Frank VOGGENREITER; Margarida M. PINHEIRO; Rui Pedro Figueiredo MARQUES (Communications of International Proceedings, 2025)
In light of increasing market volatility and digital transformation, assessing an organization’s Readiness for Change (RfC) has become a critical success factor for business transformation. However, existing frameworks for measuring readiness—such as the Awareness–Desire–Knowledge–Ability–Reinforcement (ADKAR) model, the Organizational Readiness for Implementing Change (ORIC)framework, and the Resistance to Change Scale (RTC)—often remain fragmented and overly theoretical, offering limited guidance for practical application in business contexts. This study addresses this gap by proposing a new conceptual framework that systematically integrates both individual and organizational antecedents of change readiness into a unified, business-oriented model. Building upon a comprehensive literature review and critical analysis of the aforementioned models, the paper identifies key high-impact factors—including leadership quality, communication effectiveness, psychological resilience, and digital readiness—as essential components of change readiness. Methodologically, the study develops a structured questionnaire designed to assess 19 consolidated antecedents of readiness for change, rated by practitioners across industries according to business relevance, controllability, and impact. The questionnaire underwent expert validation and pre-testing to ensure content clarity and practical applicability. Initial findings indicate that psychological factors and leadership communication are consistently rated as both highly influential and actionable in change processes. The proposed framework contributes to the literature by offering a more holistic and empirically grounded model of organizational and individual readiness for change, designed specifically for use in business environments. It provides practical guidance for organizations aiming to diagnose readiness gaps, plan targeted interventions, and enhance adaptability at multiple organizational levels.
Keywords: Organizational Readiness for Change; Change Management Assessment; Business-Centric Measurement Framework